Appraisal Realization in to All the Boys I Loved Before Novel and its Indonesian Translation - Suhartini, Sri Wulan; Nugroho, Andy Bayu (International Journal of Contemporary Studies in Education, 2023)
This study aims to identify the kinds of attitudinal systems, its realization, the translation technique, and equivalence in TT. The study was applied product-oriented research design. The data sources are the novel To All the Boys I Loved Before by Jenny Han and its Indonesian translation. The data were in the form of clauses in the ST that show attitude and their translation in the TT in the form of clauses. The data only include the expressions uttered or shown by the characters in the story. The analysis used appraisal theory by Martin and White (2005), translation techniques by Molina and Albir (2002), and equivalence by Bell (1991). Based on the type of attitudinal system, it was found that all types of attitudinal systems, namely affect, judgment, and appreciation appear in the novel between ST and TT which has relatively the same percentage. Affect has the highest percentage especially in un/happiness and in/security both texts. In terms of the realization of attitudinal system, it is found that the most used frequency is inscribed realization is more frequently use than invoked realization. Both have relatively the same percentage between ST and TT. The target text applied five translation techniques to translate the emotion or feeling in the attitudinal system. The translation techniques used are literal translation (50.7%), amplification (21.7%), modulation (18.5%), establish equivalent (4.7%), and adaptation (4.3%). The translation show found fully equivalent meaning (87.0%), partial equivalent meaning (11.6%), and different meaning (1.4%)